2004
DOI: 10.1016/j.cct.2003.08.014
|View full text |Cite
|
Sign up to set email alerts
|

The UCSD Statin Study: a randomized controlled trial assessing the impact of statins on selected noncardiac outcomes

Abstract: There has been persistent controversy regarding possible favorable or adverse effects of statins or of cholesterol reduction on cognition, mood and behavior (including aggressive or violent behavior), muscle function, and quality of life. The UCSD Statin Study seeks to ascertain the beneficial or adverse effects of statin cholesterol-lowering drugs on a set of noncardiac endpoints, including cognition, behavior, and serotonin biochemistry. The study will enroll 1000 subjects (minimum 20% female) of mixed ethni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 133 publications
(125 reference statements)
1
29
0
1
Order By: Relevance
“…221 At the end of the scheduled treatment period, the well- In addition, a randomized placebo-controlled trial among 1016 individuals without cardiovascular disease or diabetes has been conducted specifically to assess the effects of statin therapy on cognition (as well as on several outcomes related to mood and behaviour). 256 In that trial, the patients were allocated simvastatin 20 mg daily, pravastatin 40 mg daily or placebo for 6 months, with the administration of a that the statin regimens tested were not associated with adverse effects on cognitive function, albeit the duration of exposure was comparatively short. 258 Qualitative and quantitative systematic reviews of available evidence from randomized trials have also not found evidence of any adverse effects of exposure to statin therapy on a wide range of different cognitive measures.…”
Section: Memory and Other Aspects Of Cognitionmentioning
confidence: 99%
“…221 At the end of the scheduled treatment period, the well- In addition, a randomized placebo-controlled trial among 1016 individuals without cardiovascular disease or diabetes has been conducted specifically to assess the effects of statin therapy on cognition (as well as on several outcomes related to mood and behaviour). 256 In that trial, the patients were allocated simvastatin 20 mg daily, pravastatin 40 mg daily or placebo for 6 months, with the administration of a that the statin regimens tested were not associated with adverse effects on cognitive function, albeit the duration of exposure was comparatively short. 258 Qualitative and quantitative systematic reviews of available evidence from randomized trials have also not found evidence of any adverse effects of exposure to statin therapy on a wide range of different cognitive measures.…”
Section: Memory and Other Aspects Of Cognitionmentioning
confidence: 99%
“…Lower serotonergic function may mediate this link (Golomb et al, 2002) and depletion of membrane cholesterol has been demonstrated to adversely effect serotonin transporter activity (Scanlon et al, 2001). Additionally, cholesterol may influence illness and behavior via its important role as a component of the myelin sheath, a precursor for steroid hormone synthesis, and a constituent of cell membranes with subsequent roles in transmembrane exchange, enzyme function, and neurotransmitter receptor expression (Golomb et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Severe irritability and aggression with statin usage in six patients were also reported by Golomb et al (2004a). There is an ongoing double-blind, placebo-controlled clinical trial with selected 1,000 non-cardiac patients that will be available for assessing the impact of the statins in cognitive functions, personality, sleep, behavioral irritability, and blood serotonin levels correlated with aggression (Golomb et al 2004b).…”
Section: Discussionmentioning
confidence: 99%